Chronic Atrophic Gastritis and Intestinal Metaplasia: A Latin American Perspective - Arnoldo Riquelme; Felipe Silva; Diego Reyes; Gonzalo Latorre (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Gastric cancer (GC), a significant cause of mortality globally, is the leading cause of cancer-related deaths among Latin American men. GC is usually diagnosed at an advanced stage; therefore, therapeutic options are limited, and prognosis is poor. Helicobacter pylori infection remains the primary risk factor for GC; therefore, primary prevention directed toward diagnosis and treatment (“test-and-treat” strategy) is important. Western medicine guidelines recommend esophagogastroduodenoscopy (EGD) for at-risk individuals aged >40 years with regular surveillance in patients with gastric premalignant conditions (GPMC). However, limited availability of EGD in Latin America necessitates development of risk stratification tools to minimize the endoscopic burden. Results from the Chilean “Endoscopic Cohort and Histological Operative Link on Gastric Assessment (OLGA) Staging” (ECHOS study), propose endoscopic surveillance of advanced GPMC (OLGA/Operative Link for Gastric Intestinal Metaplasia [OLGIM] stages III–IV) with reliable risk stratification to facilitate early GC detection. Ensuring high-quality EGD and enhanced diagnostic yield of GPMC is essential. GPMC grading tools, such as the Kimura-Takemoto or Endoscopic Grading of Gastric Intestinal Metaplasia classification, should be incorporated into the regular risk assessment protocol. However, obtaining mapping gastric biopsies using standardized methods such as the updated Sydney System biopsy protocol, followed by grading of chronic atrophic gastritis with or without intestinal metaplasia using the OLGA and OLGIM staging systems are preferred for GC risk stratification. Recent GC prevention strategies recommended in Chile include a “test-and-treat” approach for H. pylori in individuals aged 35–44 years and combined H. pylori/pepsinogen I–II serology and EGD evaluation in patients aged >45 years to optimize the limited preventive resources available in the region.